2022
DOI: 10.3390/nutraceuticals2040027
|View full text |Cite
|
Sign up to set email alerts
|

Lemna as a Sustainable, Highly Nutritious Crop: Nutrient Production in Different Light Environments

Abstract: Development of a nutritious, sustainable food source is essential to address worldwide deficiencies in human micronutrients. Aquatic floating plants (e.g., species in the family Lemnaceae, duckweeds) are uniquely suited for area-efficient productivity with exceptionally high rates of growth and nutritional quality. Here, we provide an overview of the role of dietary micronutrients (with a focus on carotenoids) in human health and the promise of Lemnaceae as sustainable crops. We examine the effect of growth li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 103 publications
1
7
0
Order By: Relevance
“…Overall frond protein content was also lower under elevated CO 2 in the presence of continuous high light (Figure 4j), albeit to a lesser extent than chlorophyll or carotenoid levels. This finding is likely unique to duckweed and is consistent with the role of Ribulose 1,5-bisphosphate Carboxylase/Oxygenase (RuBisCO), the predominant protein in fronds, not only in photosynthesis but also as a vegetative storage protein in duckweed [53] that is maintained at high levels across a wide range of growth light environments [54,55]. This welcome finding thus illustrates the unique ability of duckweed to maintain high protein content under elevated CO 2 .…”
Section: Response Of Inoculated Lemna Plants Under High Light and Amp...supporting
confidence: 74%
See 1 more Smart Citation
“…Overall frond protein content was also lower under elevated CO 2 in the presence of continuous high light (Figure 4j), albeit to a lesser extent than chlorophyll or carotenoid levels. This finding is likely unique to duckweed and is consistent with the role of Ribulose 1,5-bisphosphate Carboxylase/Oxygenase (RuBisCO), the predominant protein in fronds, not only in photosynthesis but also as a vegetative storage protein in duckweed [53] that is maintained at high levels across a wide range of growth light environments [54,55]. This welcome finding thus illustrates the unique ability of duckweed to maintain high protein content under elevated CO 2 .…”
Section: Response Of Inoculated Lemna Plants Under High Light and Amp...supporting
confidence: 74%
“…As stated above, plant carotenoid content-with respect to the important human micronutrients lutein and provitamin A (β-carotene)-is highest under low growth light intensity in duckweed [38,56] as well as other plants. However, unlike terrestrial plants, duckweed can be grown under low light without a decline in RGR and with a maximally high protein content per dry mass [55]. In contrast to land plants, Lemna thus grew similarly fast, with the same light-and CO 2 -saturated photosynthetic capacity and as much protein per frond area (and more per dry biomass), under low versus high growth light intensity [56,57].…”
Section: Multiple Advantages Of Growing Duckweed Under Low Light Inte...mentioning
confidence: 99%
“…Investigations conducted by Appenroth et al [32,54] and our previous study [11] demonstrated similar levels of the analyzed carotenoids. According to Polutchko et al [55] and Stewart et al [56], duckweed production can provide a significant amount of green mass rich in nutrients, containing an attractive mixture of carotenoids and polyphenols, which supports its viability as a feed supplement for animals.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in photosynthetic capacity on a frond area basis was associated with a concomitant matching increase in dry biomass per frond area, such that photosynthetic capacity on a dry biomass basis remained the same ( Table 1 ). This response is similar in its time course and features to that of land plants for a comparison of low- versus high-light-grown plants, where photosynthetic capacity and dry biomass per leaf area are greater in high versus low light in proportion with each other, resulting in an unchanged photosynthetic capacity on a dry biomass basis [ 79 ]. It can be concluded that L. minor did undergo acclimatory changes in photosynthetic capacity in response to a sudden increase in nutrient supply in the medium.…”
Section: Acclimation To Other Environmental Factors In Land Plants An...mentioning
confidence: 97%